A systematic review of nutrient composition data available for twelve commercially available edible insects, and comparison with reference values. (January 2016) - Payne, Charlotte L.R.; Scarborough, Peter; Rayner, Mike; Nonaka, Kenichi
Abstract: Background: Edible insects have been proposed as a more environmentally sustainable and nutritious alternative to conventional livestock. In response to the promotion of insects as food and feed by the Food and Agriculture Organization of the United Nations, insect agriculture is now a growing industry across the world. Yet information regarding the nutritional composition of commercially available insect species is disparate in terms of data quality, the location of published sources, and the form in which data is presented. Scope and approach: We conducted a systematic review of all published nutrient composition data for twelve selected species of commercially available edible insect. Our objective was to create a nutrient composition table in line with INFOODS/EuroFIR guidelines, and to present the results in a standardised form that is easily comprehensible for nutritionists and policy-makers. Key findings and conclusions: Our results expose the low quality of data describing edible insect nutritional composition, when compared to INFOODS/EuroFIR recommendations. This calls attention to the need for greater adherence to international guidelines in this field. The data that were included in our final table show clear within-species variation in the proportion of both macro- and micronutrients. This highlights the importance of external factors such as feed and ecology in determining nutrient composition. Highlights: We select twelve currently commercially available edible insects including farmed and wild-caught species. We conduct a systematic review of literature and databases describing nutrient composition of all twelve species. We present the results of our review as nutrient composition tables, expressed as a percentage of daily reference values. Currently available insect nutrient composition data is of predominantly low quality according to international guidelines. Depending on species, insects have high quantities of both 'harmful' and 'beneficial' nutrients. More research is needed.